Characterization of cool flame products during the low temperature oxidation of n-pentylbenzene. (15th August 2023) - Zeng, Meirong; Gao, Jigang; Zhou, Zhongyue; Ye, Lili; Yang, Jiuzhong; Yuan, Wenhao; Qi, Fei
Highlights: Low temperature oxidation of n -pentylbenzene was investigated in an atmospheric jet stirred reactor by using SVUV-PIMS. Around 70 intermediates were detected, including highly oxygenated molecules and hydroperoxides formed from third O2 addition process. Structures of phenyl alkyl hydroperoxides, ketohydroperoxides, olefinic hydroperoxides, ketodihydroperoxides were identified by combining experimental and theoretical analysis. A comprehensive low temperature oxidation reaction network was proposed for n -pentylbenzene. Abstract: Radical chain recycling reactions represent a general topic in the chemistry of combustion, atmosphere, polymerization and so on. The nature and amount of OH radicals that generated by hydroperoxides during the oxidation of alkanes have been proven to drive the overall reactivity by enhancing the chain recycling steps. While low temperature oxidation kinetics of alkanes have been widely investigated, the comprehensive intermediates distribution during the low temperature oxidation of n -alkylbenzenes remains unexplored. This work selects n -pentylbenzene as a simple representative to investigate the low temperature oxidation kinetics of n -alkylbenzenes, especially intermediates and reactions that control the reactivity. The experiments were performed with a jet-stirred reactor coupled with the synchrotron vacuum ultraviolet radiation photoionization mass spectrometry (SVUV-PIMS). Around 70 intermediates, including phenyl hydroperoxides and highly oxygenated molecules (HOMs) were detected. By combining theoretical calculations and kinetic analysis, potential compositions and structures of key intermediates were identified and categorized into groups by their characteristic molecular formulae and chemical functionalities, such as C11 H16 On, C11 H14 On, C11 H10 On . Fingerprint hydroperoxides, including phenyl alkyl hydroperoxides, ketohydroperoxides, olefinic hydroperoxides, ketodihydroperoxides, were revealed to be formed from the characteristic first, second and third O2 addition and sequential reactions. These hydroperoxides play a dominant role in driving the low temperature oxidation reactivity by generating active OH radicals. The present experimental evidence, including the negative temperature coefficient behavior of n -alkylbenzenes as well as featured HOMs from the third O2 addition, extend the conceptual reaction schemes proposed in alkanes towards the oxidation of n -alkylbenzenes.